Domperidone effective in preventing rivastigmine-related gastrointestinal disturbances in patients with Alzheimer's disease - Kano O (Dove Medical Press, 2013)
Osamu Kano,1 Yoshihisa Urita,2 Hirono Ito,1 Takanori Takazawa,1 Yuji Kawase,1 Kiyoko Murata,1 Takehisa Hirayama,1 Ken Miura,1 Yuichi Ishikawa,1 Tetsuhito Kiyozuka,3 Jo Aoyagi,3 Yasuo Iwasaki11Department of Neurology, 2Department of General Medicine and Emergency Care, Toho University Omori Medical Center, Tokyo, Japan; 3Department of Neurology, Federation of National Public Service Personnel Mutual Aid Associations, Mishuku Hospital, Tokyo, JapanObjective: While acetylcholinesterase inhibitors, such as donepezil, galantamine, and rivastigmine, are beneficial in treating behavioral symptoms of patients with Alzheimer's disease (AD), their dose-limiting effects include gastrointestinal disturbances, such as nausea, vomiting, and diarrhea. We aimed to predict the occurrence of these gastrointestinal disturbances with rivastigmine therapy for optimal drug choice and improved compliance.Materials and methods: Thirty patients with mild-to-moderate AD (scores 10–22 on the Mini-Mental State Examination) were administered a rivastigmine 18 mg patch with domperidone 30 mg (RWD) and without domperidone (RWOD; n = 15 each) for 20 weeks. Gastrointestinal disturbances were evaluated using a frequency scale for symptoms of gastroesophageal reflux disease (FSSG), Bristol stool form scale, laboratory data (hemoglobin, albumin, total cholesterol), body weight, and amount of food intake.Results: After 12 weeks, FSSG scores were higher in the RWOD group compared to baseline scores; however, no significant differences were noted between the RWD and RWOD groups. We then subdivided each group based on high and low baseline scores; the RWOD high-score (≥4) subgroup showed increased FSSG after 12 weeks compared with the baseline score. In both RWD and RWOD groups, the low-score (≤3) subgroups showed no changes during the dose-escalation phase.Conclusion: For AD patients with higher FSSG scores at baseline, domperidone was effective in preventing rivastigmine-related gastrointestinal disturbances.Keywords: Alzheimer's disease, acetylcholinesterase inhibitors, domperidone, gastroesophageal reflux disease, gastrointestinal disturbance, rivastigmine